EFEKTIVITAS PELAKSANAAN PEMBERDAYAAN MASYARAKAT MISKIN MELALUI PROGRAM BANTUAN RUMAH TIDAK LAYAK HUNI OLEH DINAS SOSIAL TENAGA KERJA DAN TRANSMIGRASI DI KABUPATEN PADANG LAWAS UTARA - LISAINI . (Welfare StatE, 2013)
This thesis is titled "Empowering the Poor Implementation Effectiveness Through Improper Assistance Program Home habitation By Social Service Manpower and Transmigration in Padang Lawas regency North". The purpose of this study was to determine the effectiveness of the empowerment of the poor through housing assistance programs are not suitable for habitation by the Department of Social Welfare Manpower and Transmigration in Padang Lawas regency North. Type of research used in this research is descriptive method. Meanwhile, data analysis techniques using single table and described quantitatively by Likert scale. The conclusions obtained through analysis of the data that the effectiveness of the aid program uninhabitable by the Department of Social Welfare Manpower in Padang Lawas regency North is not or has not been effective. The calculation result is said to be ineffective seen from several measurements that have been made, from the understanding of the program as much as 1,24, from 1,51 as targeting accuracy, timeliness of as much as 0,46 from 0,53 as much as the goals and of real change as much as 0,60.   Keywords: Effectiveness, Empowerment of the Poor, Not Livable house.